The Effect of Community Participation on the Effectiveness of the Implementation of Road Development in Sibaganding Village, Garoga District - Frengki Tambok Marpaung; Joan Berlin Damanik (Jurnal Mantik, 2021)
Community participation in the implementation of development programs is one form of public concern for the implementation of development. Community participation is also one of the factors that influence the success or failure of development programs in a region. Community participation is needed because the government program that is being implemented is none other than the community. The community should participate together with the government to provide a role to increase and facilitate the implementation of development programs. The involvement or participation of all levels of society in providing participation in any development program can be in the form of contributing thoughts or giving ideas of physical involvement or energy, as well as sharing in the results of the development program itself.The purpose of this study was to determine how the influence of community participation on the effectiveness of the implementation of road construction in Sibaganding Village, Garoga District. This type of research is an associative study, namely research conducted to determine the effect of two or more variables. Data collection was carried out by means of questionnaires, interviews and documentation. Data analysis techniques are: simple correlation, simple regression and t test. The result of the research is that there is a positive relationship between Community Participation and the Effectiveness of the Implementation of Road Development of 0.759. The coefficient of determination (R2) is 0.576. The regression results are: Y = 15,456 + 0.810 (X), the result of t count (10,863)> t table (1.